IMMUNOLOGICAL AND MORPHOLOGICAL PREDICTORS OF CLINICAL HETEROGENEITY OF PATIENTS WITH GRAVES' DISEASE (BASED ON RESEARCH OF THE THYROID GLAND OPERATIONAL MATERIAL) - T. V. Saprina; T. S. Prokhorenko; N. V. Ryazantseva; I. N. Vorozhtsova; S. Yu. Martynova; A. N. Dzyuman; A. P. Zima; O. S. Popov; I. A. Khlusov; K. T. Kasoyan; I. P. Shabalova (Бюллетень сибирской медицины, 2015)
Very little research is devoted to the study of communication systemic immunological changes and local immunological changes in the tissue of the thyroid in autoimmune thyrophaties. The goal of the research was to establish immunologic and morphologic predictors of clinical course and functional outcomes of Graves’s disease (GD).Material and methods. We examined 45 patients with GD (14 men and 31 women) aged 18–55 years (47.0 (35.0–53.0)) years, matching the following criteria: a verified diagnosis GD, accommodation in Tomsk oblast and the Tomsk not less than 10 years, the patient's consent for the study. The control group included 30 people, with an average age of (45.3 ± 5.6) years and was comparable by age and sex with GD patients. The study included: definition of the standard for GD hormonal and serological profile (free T4, free T3, and TSH, antibodies to TPO, antibodies to the TSH receptor), the cultivation of mononuclear leukocytes in complete culture medium within 24 hours with subsequent determination of interleukins concentrations (IL-2, IL-4, TNF-alpha) in culture medium using enzyme-linked immunosorbent assay, determination of the number of blood cells carrying membrane-bound receptors to IL-2, IL-4, TNF-R1 by flow laser cytometry on cytometer BD FACS Canto tmΙΙ (USA) using labeled monoclonal antibody, the standard postoperative histological examination of thyroid gland tissue samples and immunohistochemical detection in samples of thyroid tissue receptors to IL-2, IL-4, TNF-alpha.Results. On the basis of the received results it is possible to allocate 2 clinical-immunologic and morphologic cluster of autoimmune hyperthyroidism syndrome in patients with clinical diagnosis of GD. The first includes the formation of 1 and 2 histological options GD (minimally expressed monocytes infiltration, lack of oncocytic transformation of thyroid epithelium), with some clinical characteristics (persistent and pronounced hyperthyroidism, the large size of goiter, higher titer of receptor TSH-antibody and smaller TPO-antibody, diffuse nature of the lesion), and the second – is represented by 3d histological option with oncocytic restructuring of follicular epithelium, expressed the monocyte/macrophage infiltration with the TNF-RI expression and clinical patterns, including: the older age group of patients, the smaller size of goiter, the emergence of “pseudo nodes” ultrasound, reflecting the presence of lymphoid follicles-infiltrates, more lenient for hyperthyroidism. Probably, that the 2nd cluster is a combination of “classical GD” with autoimmune thyroiditis, however, a set of clinical and laboratory-instrumental signs led to the fact that these patients were in the group of GD patients.Conclusion. This approach (combining study of indicators of systemic and local tissue-specific autoimmune inflammation) is a promising from the point of view of separate parts coverage in the autoimmune thyroids diseases pathogenesis, approximating researchers to develop immune based therapeutic technologies.